Saving Santa = Zamanda yolculuk - Joosen, Leon; Seelman, Aaron (Gateway Films : Prana Animation Studios, 2013)
A lowly stable elf finds that he is the only one who can stop an invasion of the North Pole by using the secret of Santa's Sleigh, a TimeGlobe, to travel back in time to Save Santa - twice.
3-6.
K-3.
Language : Turkish, English.
Subtitle : Turkish, English.
Keywords: Christmas -- Movie; Elves -- Movie; Movie -- animated films; Movie -- Kids/Family.; Santa Claus. -- Movie